Does the likely perpetrator's marital status matter in engaging in the act of sexual harassment? - Kenny, Kamal; Abu Samah, Asnarulkhadi (Center for Promoting Ideas, 2011)
This study explored men’s likelihood to sexually harass a female colleague in a given context. Participants were 900 male non-academic employees working in 3 major Research Universities in Malaysia. As sexual harassment is a phenomenon that has always been looked from a woman’s perspective, this study had looked from the men’s perspective of understanding the likelihood in engaging in a array of actions that are considered an act of sexual harassment. The major finding of the study shows that men, regardless of marital status view many acts of sexual harassment as acceptable and the findings depict that there is no distinct differences between men of both the married and single group in their likelihood to sexually harass their female colleagues as contrary to past research on sexual harassment that have suggested that single men have a higher tendency to sexually harass due to his marital status.